Enhanced and unified anatomical labeling for a common mouse brain atlas - Uree Chon (Nature Portfolio, 2019)
Anatomical brain atlases elucidate the anatomical and functional organisation across species but different atlases have conflicting anatomical border and 3D coordinates. The authors integrated two atlases into a unified and highly segmented anatomical labelling system of the mouse brain.